Smoke-free legislation in Malaysia: a comprehensive review - Zainol Abidin, Najihah; Zulkifli, Aziemah; Zainal Abidin, Emilia (Environmental and Occupational Health Society, 2016)
Introduction: As a party to the World Health Organization - Framework of Convention on Tobacco Control (WHO FCTC), Malaysia has introduced steps in the control of tobacco use in public places through its smoke- free legislation (SFL). Objective: The purpose of this review is to briefly summarise the implementation of SFL in Malaysia, the efforts from every angle of the community and to address the gaps and new challenges faced in ensuring the effectiveness of this well-constructed legislation. Results: Well-structured and positive commitments in protecting the public from the health hazards of smoking and second-hand smoke (SHS) exposure have been shown by the Malaysian government. However, the level of compliance is an area of concern. Since e-cigarettes have been introduced to the market, it brings along new challenges in the implementation of the current SFL. Thus, treating e-cigarettes in the same manner with conventional cigarettes will help to maintain the strength of the current SFL and allowing the authority to focus on the enforcement for the successfulness of the implementation. Conclusions: Malaysia has taken a proactive action in protecting its people from the adverse effects from tobacco. The compliance level to SFL implementation thus far was unable to show its positive effects in protecting the health of the public. Empowering the local authority in its ability to perform enforcement is suggested to help improve the effectiveness of the existing SFL.